Virtual environments as an assessment modality with pediatric ASD populations: a brief report. Issue 8 (17th November 2018) - Duffield, Tyler C.; Parsons, Thomas D.; Landry, Allisen; Karam, Shaza; Otero, Tiffany; Mastel, Sarah; Hall, Trevor A.
ABSTRACT: Virtual environments (VEs) have demonstrated promise as a neuropsychological assessment modality and may be well suited for the evaluation of children suspected of having an autism spectrum disorder (ASD). Some recent studies indicate their potential for enhancing reliability, ecologically validity, and sensitivity over traditional neuropsychological evaluation measures. Although research using VEs with ASD is increasing to the degree that several reviews of the literature have been conducted, the reviews to date lack rigor and are not necessarily specific to cognitive or neuropsychological assessment as many focus on intervention. The aim of this project was to comprehensively examine the current literature status of neuropsychological assessment in pediatric ASD using VEs by conducting a systematic review. Specifically, psychometric comparisons of VEs to traditional neuropsychological assessment measures that examined reliability, validity, and/or diagnostic accuracy for pediatric individuals, age 18 and below, with ASD were sought. The search using key words yielded 899 manuscripts, 894 of which were discarded for not meeting inclusion criteria. The remaining five met exclusion criteria. Therefore, the systematic review was modified to a brief report. These findings (or lack thereof) indicate a significant gap in the literature in that psychometric comparisons of these tools for the neuropsychological assessment of pediatric individuals with ASD are lacking. An important future direction of research will be extending the demonstrated incremental validity of VE neuropsychological assessment with other neurodevelopmental (e.g., attention-deficit/hyperactivity disorder) and adult populations to pediatric ASD populations.